Transformational Leadership Dimensions and Job-Based Psychological Ownership as Facilitators in International Intrapreneurship of Family Firms - Giang, Huynh Thi Thuy; Dung, Luu Tien (The South East Asian Journal of Management, 2021)
Research Aims: The purpose of this study is to examine the effects of transformational leadership dimensions (TL) and job-based psychological ownership (PO) on nonfamily employee international intrapreneurship in family firms (FFs). Design/methodology/approach: The study adopted a sample of 246 key role nonfamily employees at 118 family-owned export and import SMEs in Ho Chi Minh City, Vietnam. The data are analysed using a partial least squares structural equation modelling (PLS-SEM). Results: The article identifies four dimensions of TL and international intrapreneurship in which both concepts are interlinked. Job-based PO plays a significant role in the TL dimensions' effects on international intrapreneurship. Theoretical Contribution/Originality: The article establishes the mechanism by which TL constructs influence nonfamily employee international intrapreneurship actions by examining the mediating role of employee job-based PO in FFs. Managerial Implication in the South East Asian context: FFs need to develop the architecture and mechanisms for enabling nonfamily employees' international intrapreneurship to be committed to TL constructs and job-based PO. Research limitation & implications: This article contributes to international business theory by interpreting the export trading results of FFs using entrepreneurship theory. However, each stage of FFs international business requires a unique set of resources. As a result, it is necessary to incorporate theoretical perspectives from both domains to explain each internationalisation stage of FFs adequately.